IoT Service Search using MQTT Protocol - Najeeb, Nihaala; Joseph, Shelbi (International Journal of Computer Sciences and Engineering, 2019)
The Internet of Things (IoT) visualize seamlessly connecting the physical objects with the Internet. This in turn combines the physical world into the digital world. There are several mechanisms available that reduces the need for external human intervention for maintaining and configuring deployed. They must be scalable and efficient, since the number of deployed objects is expected to grow exponentially in the next few years. Resource discovery is a problem of ﬁnding useful devices and their services in order to accomplish a task, and it constitutes a major challenge for IoT. In this paper a survey on various service discovery mechanisms is performed and an MQTT protocol based IoT service search has been proposed. The proposed work uses a clustering and optimal distribution mechanism on the IoT services to find the optimal distribution value and return the services. Experimental results have shown significant improvement in service discovery time.